(untitled) (Journal of Telenursing (JOTING), 2021)
This study aims to describe the knowledge of stimulation of early childhood development by the teacher. The research method used in this research is a quantitative method with a cross-sectional research design using the Chi-Square. The population in this study was 20 teachers in PAUD Aisyiyah X Gading Cempaka. The sampling technique used the total sampling technique. The results showed that the description of PAUD teacher knowledge about early childhood development stimulation in PAUD Aisyiah X Bengkulu City from 20 teachers, the excellent knowledge category was 11 respondents (50%), less than eight respondents (20%) and enough as many as two respondents (10%). In conclusion, the description of PAUD teacher’s knowledge about stimulating early childhood development in PAUD Aisyiah X Bengkulu City is mostly classified as good knowledge. Keywords: Teacher, Knowledge, Development Stimulation